Mathematical cognition - Royer, James M., 1941- (Emerald Publishing Limited : Information Age Pub., 2003)
This book is divided into seven chapters including: a broad overview of mathematical cognition; development of mathematical cognition; working memory, automaticity and mathematical problem solving; mathematical problem solving; and methematical learning disabilities.
Keywords: Mathematics -- Study and teaching (Preschool); Mathematics -- Study and teaching (Primary); Cognition in children.; Education -- Teaching -- Subjects -- Mathematics.; Teaching of a specific subject.; Teaching of reading, writing and numeracy.; Educational: Mathematics and numeracy.; elektronické knihy; electronic books